Enhanced Flexural Strength and Modules of Elasticity of Lightweight Pumice Aggregate Concrete - Shakir A. Khudair; Mohammed A. Basher (Genius Journals, 2023)
Low density and thermal resistance are important characteristics of pumice aggregate concrete. This type of concrete is known to be weak in most of its mechanical properties, the most important of which are bending and modulus of elasticity. It has become necessary to focus on improving the mechanical properties this type of concrete. To increase the flexural strength and modules of elasticity of Lightweight pumice aggregate concrete, steel fiber in various ratios were added to pumice aggregate concrete. Five combinations were chosen to be flexural strength enhanced. The five chosen mixes each received 0.5, 0.75, 1%, of steel fiber. Considered are the mechanical characteristics of produced concrete. Results showed that steel fibers improved flexural strength is more than 50% when added steel fiber 1% by volume compared to lightweight pumice aggregate concrete mix without fibers, and modules of elasticity increased 30% When added 1% steel fiber to mixes compared with mixes without fibers.
Keywords: Pumice aggregate concrete; Lightweight concrete; Steel fiber